(untitled) (Journal of Dhaka Medical College, 2021)
Background: Ventricular arrhythmias (VA) are among the most feared complications of coronary artery disease (CAD) and one of the major contributors of death in CAD patients. Antiarrhythmic drug (AAD) therapy is required for recurrent significant VA in the absence of need for further revascularization. But all AADs do not have the same efficacy against life threatening VA and supraventricular arrhythmias (SVAs). Methodology: All (50) patients admitted in the department of Cardiology, BSMMU with ventricular arrhythmias with CAD fulfilling the inclusion and exclusion criteria were included in the study. Informed written consent was taken from each patient before enrollment. Detailed history was taken and relevant physical examinations were done. Loading dose followed by maintenance dose of amiodarone was given and recorded. Relevant lab investigations were performed and recorded in predesigned semi-structured data collection sheet. Symptomatic improvement was assessed, relevant physical examination was done and lab investigations were performed at 1, 3 and 6 month follow up. After editing data analysis was carried out by using the Statistical Package for Social Science (SPSS) version 23.0 windows software. Results: The mean age was found 57.7±8.0 years with a range of 45 to 78 years. Almost two third (62.0%) patients were male and 19(38.0%) patients were female. Male female ratio was 1.6:1. Almost three fourth (74.0%) patients had chest pain, 15(30.0%) had palpitation and 11(22.0%) had shortness of breath. Two third (66.0%) patients had hypertension, 23(46.0%) had dyslipidemia, 17(34.0%) had smoking and 9(18.0%) had diabetes mellitus. Twenty nine (58.0%) patients had family history of IHD. The difference was statistically significant (p<0.05) when compared to baseline. Regarding arrhythmia, 45(90.0%) patients was found to have PVC in baseline and 3(6.4%) at 6th month. The reduction of PVC and VT at six month were statistically significant (p<0.05) when compared to baseline. Regarding outcome 2(4.1%) patients died, one patient dropped out due to thyroid dysfunction and 47 were alive. Conclusion: In conclusion it was found that different forms of ventricular arrhythmias like PVCs, VT were significantly reduced gradually with amiodarone therapy at 6th month follow up. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 158-164